Red Shift of Side-Polished Fiber Surface Plasmon Resonance Sensors With Silver Coating and Inhibition by Gold Plating - Mingquan Li; Zhiyong Bai; Feng Zhang; Maoxiang Hou; Ying Wang; Changrui Liao; Wei Jin; Yiping Wang (IEEE Photonics Journal)
The degeneration of Ag coatings on the polished surfaces of side-polished fibers (SPFs) with different surface topographies, and its inhibition by Au plating were studied by the time-dependent red shift of the resonance wavelength of SPF surface plasmon resonance (SPR) sensors. The surface topography determines the Ag-particle distribution, and affects the optical performance. The resonance wavelength of rough and smooth samples demonstrates a red shift over time. However, the service lifetime of an Ag-SPR sensor with a rough surface is less than 48 h because an abundance of coating flakes destroys the integrity of the Ag coating, and accelerates oxidation. Degeneration does not decrease its sensitivity. The smooth surface retards the degeneration rate. A thin Au plating decreases the resonance bandwidth for the rough surface, and provides a resonance wavelength near the middle of the ideal range between 533 and 620 nm. The position of the resonance wavelength can be adjusted by changing the proportions of Ag and Au in the compound coating. The Au plating retards the rate of Ag degeneration, where the maximum degeneration rate of a pure Ag coating is 3.5 times greater that of an Ag–Au compound coating between 96 and 192 h.